An Analysis On Characteristics And Performance Of Tourism Related Smes In Lenggong Valley, Perak - Munira, Mhd Rashid (2014)

(untitled)
The existence of businesses create a potential feature to improve the competitiveness of UNESCO World Heritage Site of Lenggong Valley as a world tourism destination. Hence, this study intends to analyse the characteristics and measure performance of tourism related SMEs in Lenggong Valley, Perak. Kewujudan perniagaan mewujudkan satu ciri yang berpotensi untuk meningkatkan daya saing Lembah Lenggong Tapak Warisan Dunia UNESCO sebagai sebuah destinasi pelancongan dunia. Oleh itu, kajian ini bertujuan untuk menganalisis ciri-ciri dan mengukur prestasi PKS berkaitan pelancongan di Lembah Lenggong, Perak.